Tinjauan Yuridis Rapat Umum Pemegang Saham Dalam Perseroan Terbatas (PT Tertutup) - ., Diana; Widjaja, Gunawan; Rusli, Hardijan (Pelita Harapan University, 2004)
There are many types of company in Indonesia. Limited Company is the most favourable type for owners because their responsibility is limited still they have the privilege to replace or shift their shares. Basically, Limited Company is a cooperation agreement made by the founders. Generally, the bargaining position of each founder is not always the same. This leads to the arising of 2 different groups, i.e. the majority shareholders and the minority shareholders. Commonly, the majority shareholders is the owner who has more than 50% of the shares in a limited company. Hence, the majority shareholder holds the strongest position in decision making in general meeting of shareholders and have the advantage to decide any decision whether would be a positive and negative to the company and minority shareholders. In thus circumstance, to protect minority rights and interest, the limitation and restriction to the majority owners rights and needed. UUPT gives protection to the minority shareholders in General Meeting of Shareholders through the minimum quorum limitation. Even so, in the real situation, such regulation is not adequate to protect minoritys right. This script would view some of the General Meeting of Shareholders regulation and implementation in Indonesia; and also to comment and give advice to settle some of these matters.